2016
DOI: 10.1111/nmo.12893
|View full text |Cite
|
Sign up to set email alerts
|

Nausea and vomiting in gastroparesis: similarities and differences in idiopathic and diabetic gastroparesis

Abstract: Nausea and vomiting are classic symptoms of gastroparesis. It is unclear if characteristics of nausea and vomiting are similar in different etiologies of gastroparesis. Aims Describe characteristics of nausea and vomiting in patients with gastroparesis; and determine if there are differences in nausea and vomiting in diabetic (DG) and idiopathic gastroparesis (IG). Methods Gastroparetic patients enrolling in the NIDDK Gastroparesis Registry underwent assessment with history and questionnaires assessing symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 27 publications
1
58
1
1
Order By: Relevance
“…In a prior study of ours, we described the characteristics of nausea and vomiting in patients with gastroparesis [21]. The characteristics of nausea (severity, timing) were similar in diabetic and idiopathic patients.…”
Section: Discussionmentioning
confidence: 75%
“…In a prior study of ours, we described the characteristics of nausea and vomiting in patients with gastroparesis [21]. The characteristics of nausea (severity, timing) were similar in diabetic and idiopathic patients.…”
Section: Discussionmentioning
confidence: 75%
“…Since some patients had vomited their test-meal, their exclusion could have led to a selection bias since excluding the more severe patients imply not reflecting anymore the dyspeptic population of origin. 40 However, the number of those patients is very small (4 patients, 2%). Finally, we did not realize any subgroup analysis according to treatments, especially as patients had to stop every treatment that could interact with the measurement of gastric emptying before the test.…”
Section: Discussionmentioning
confidence: 97%
“…Blocking NK-1R in smooth muscle could increase gastric emptying, as it has been reported that aprepitant can increase gastric accommodation volume and maximum calorie volume tolerated in healthy volunteers 28 . Delayed emptying is a predictor of more severe upper gastrointestinal symptoms 29,6 ; however, improvement in gastric emptying rate does not always correlate well with improvement in symptoms 22,30,31,32,33 . The effect of gastric emptying will be assessed in future studies, although we predict tradipitant to be useful for treatment of gastroparesis with or without an effect on gastric emptying rate.…”
Section: Discussionmentioning
confidence: 98%